A Case of Giant Right Atrial Aneurysm in a Child. (July 2016) - Pawar, Ravindra S.; Tiwari, Ashish; Suresh, P. V.; Raj, Vimal; Kaushik, Pradeepkumar
Giant right atrial aneurysm is a rare entity in infants and children. It needs to be distinguished from an atrial diverticulum, which can have similar presentation. Generally, an incidental finding in children, it can present with varied symptoms. We report a case of a giant right atrial aneurysm in an asymptomatic child with a large clot in the dilated right atrium, who underwent successful resection of the atrial aneurysm.